PENYERAPAN KOSAKATA BAHASA JAWA KE DALAM BAHASA INDONESIA MASA KINI (JAVANESE VOCABULARY ABSORPTION INTO CURRENT INDONESIAN LANGUAGE) - Edi Suwatno (Balai Bahasa Sulawesi Utara, 2016)
Absorption of Javanese to Indonesian vocabulary will enrich vocabularies besides finding its similarities excluded in Indonesia language. The absorption is conducted fully or according to vocal cord or letter or its pronunciation. The absorption is conducted because the two languages have different sound system and symbol. The sound difference of both languages is stimulated by specialty of Javanese language out of Indonesia language order. Besides that, pronunciation between the two languages are different. Those two language use sound symbol called alphabet using latin writing, but there is Javanese language letter sound that Indonesia language does not have; like sound letter /th/-ţ ,/dh/-ḍ, last rounded vowel /a/-/ᴐ/, diacritics /é, è/; front unrounded vowel /ᴐ/, rounded last vowel and absorption of EYD appropriation.